Negative electrode and method of producing the same, and non-aqueous electrolyte secondary battery including negative electrode and method of producing the same

JP2025034639AActive Publication Date: 2025-03-13PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023141137
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13
Estimated Expiration
2043-08-31

AI Technical Summary

Benefits of technology

【0022】 本開示の負極によれば、優れたサイクル特性を有する非水電解質二次電池を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034639000001_ABST
    Figure 2025034639000001_ABST
Patent Text Reader

Abstract

To provide a negative electrode that can realize a non-aqueous electrolyte secondary battery with excellent cycling characteristics.SOLUTION: A negative electrode for a non-aqueous electrolyte secondary battery has an active material layer including active material particles, carbon nanotubes and a first binder. The active material particles include metal-based active material particles and carbon-based active material particles. The carbon nanotubes have a G / D ratio of 30 or more. An average length of the carbon nanotubes determined by analysis of a scanning transmission electron microscope image of the active material layer is 1.4 μm or more. The active material layer includes a mixed body in which the carbon nanotubes and the first binder are mixed. The mixed body includes a first mixed body formed on at least part of a surface of each active material particle and a second mixed body connecting a pair of the active material particles to each other.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode and a method for producing the same, and to a non-aqueous electrolyte secondary battery including the negative electrode and a method for producing the same. [Background technology]

[0002] A non-aqueous electrolyte secondary battery has a negative electrode including an active material layer. The active material layer may contain active material particles such as graphite or SiOx, and fibrous carbon such as carbon nanotubes (for example, Patent Document 1, etc.). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-99955 Summary of the Invention [Problem to be solved by the invention]

[0004] Metal-based active material particles such as SiOx have a lower electrical conductivity than graphite and expand and contract significantly during charging and discharging of a secondary battery, which deteriorates the conductive path formed between the surrounding active material particles and tends to cause deterioration of the cycle characteristics of the secondary battery. Carbon nanotubes can form a good conductive path by bridging between the active material particles, so they are used to suppress the deterioration of the conductive path. However, even when the active material layer contains carbon nanotubes, the cycle characteristics of the secondary battery may deteriorate.

[0005] An object of the present disclosure is to provide a negative electrode with which a secondary battery having excellent cycle characteristics can be obtained and a method for producing the same, as well as a nonaqueous electrolyte secondary battery including a negative electrode and a method for producing the same. [Means for solving the problem]

[0006] [1] A negative electrode for a non-aqueous electrolyte secondary battery, an active material layer including active material particles, carbon nanotubes, and a first binder; The active material particles include metal-based active material particles and carbon-based active material particles, The carbon nanotubes have a G / D ratio of 30 or more; the average length of the carbon nanotubes, as determined by analysis of a scanning transmission electron microscope image of the active material layer, is 1.4 μm or more; the active material layer includes a mixture of the carbon nanotubes and the first binder, The mixture includes a first mixture formed on at least a portion of the surface of the active material particles, and a second mixture spanning between two of the active material particles.

[0007] [2] The negative electrode according to [1], wherein a ratio of the carbon nanotubes present in the first mixture and the second mixture to a total amount of the carbon nanotubes in the active material layer, as determined by analysis of the scanning transmission electron microscope image of the active material layer, is 40% or more.

[0008] [3] The negative electrode according to [1] or [2], wherein the metal-based active material particles include one or more particles selected from the group consisting of Si, SiOx, and a composite of Si and C.

[0009] [4] The negative electrode according to any one of [1] to [3], wherein the metal-based active material particles include particles of a composite of Si and C.

[0010] [5] The negative electrode according to any one of [1] to [4], wherein the carbon nanotubes are single-walled carbon nanotubes.

[0011] [6] The negative electrode according to any one of [1] to [5], wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.

[0012] [7] The active material layer includes a second binder different from the first binder, The negative electrode according to [6], wherein the second binder contains styrene-butadiene rubber.

[0013] [8] A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of [1] to [7]. [9] A method for producing a negative electrode for a non-aqueous electrolyte secondary battery, comprising: A first step of preparing a slurry; A second step of forming an active material layer of the negative electrode using the slurry, the slurry includes active material particles, a first binder, carbon nanotubes, and water; The active material particles include metal-based active material particles and carbon-based active material particles, The carbon nanotubes have a G / D ratio of 30 or more.

[0014]

[10] The first step comprises: (1b) obtaining a kneaded body by kneading the active material particles, the first binder, the carbon nanotubes, and water to a solid content of 60 to 65% by weight; and (1c) further adding water to the kneaded body and kneading the mixture.

[0015]

[11] The first binder is at least one of carboxymethyl cellulose and polyacrylic acid, The step (1c) includes a step of kneading a second binder together with the kneaded body and the water, The method for producing a negative electrode according to

[10] , wherein the second binder contains styrene-butadiene rubber.

[0016]

[12] The first step includes, prior to step (1b), a step (1a) of dry-mixing the active material particles and the first binder to obtain a mixture; The method for producing a negative electrode according to

[10] or

[11] , wherein in the step (1b), the mixture, the carbon nanotubes, and water are kneaded.

[0017]

[13] The method for producing a negative electrode according to any one of

[10] to

[12] , wherein the kneading in the step (1b) is carried out using a stirrer having a stirring blade under conditions where the rotation speed of the stirring blade is 60 rpm or less.

[0018]

[14] The method for producing a negative electrode according to any one of [9] to

[13] , wherein the carbon nanotubes have a direct current resistance of 2000 Ω or less at 25° C. when dispersed in 0.4 wt % water.

[0019]

[15] The method for producing a negative electrode according to any one of [9] to

[14] , wherein the metal-based active material particles contain one or more types of particles selected from the group consisting of Si, SiOx, and a composite of Si and C.

[0020]

[16] The method for producing a negative electrode according to any one of [9] to

[15] , wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.

[0021]

[17] A method for producing a non-aqueous electrolyte secondary battery, comprising a step of producing a negative electrode by the method for producing a negative electrode according to any one of [9] to

[16] . Effect of the Invention

[0022] According to the negative electrode of the present disclosure, a nonaqueous electrolyte secondary battery having excellent cycle characteristics can be obtained. [Brief description of the drawings]

[0023] [Figure 1] 1 is a scanning transmission electron microscope image of an active material layer of a negative electrode according to an embodiment. [Diagram 2] 13 is a scanning transmission electron microscope image of an active material layer of a negative electrode according to another embodiment. [Diagram 3] 2 is a flowchart showing an example of a method for manufacturing a negative electrode according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In this specification, a numerical range such as "x to y" includes an upper limit and a lower limit unless otherwise specified. That is, "x to y" represents a numerical range of "not less than x and not more than y". A numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, or in a figure, etc.

[0025] (Negative electrode) Fig. 1 is a scanning transmission electron microscope image (hereinafter also referred to as "SEM image") of the active material layer of the negative electrode of the embodiment, which shows the active material layer obtained by carrying out the first step (1) of the negative electrode manufacturing method described later. Fig. 2 is a SEM image of the active material layer of the negative electrode of another embodiment, which shows the active material layer obtained by carrying out the first step (2) of the negative electrode manufacturing method described later.

[0026] The negative electrode of this embodiment (hereinafter also referred to as "the present negative electrode") is a negative electrode for a non-aqueous electrolyte secondary battery (hereinafter also referred to as "secondary battery") and includes an active material layer. The active material layer includes active material particles, carbon nanotubes (hereinafter also referred to as "CNTs"), and a first binder. The active material particles include metal-based active material particles (hereinafter also referred to as "metal-based particles") and carbon-based active material particles (hereinafter also referred to as "carbon-based particles"). The G / D ratio of the CNTs is 30 or more, and the average length of the CNTs obtained by analyzing an SEM image of the active material layer is 1.4 μm or more. The active material layer includes a mixture of the CNTs and the first binder. The mixture includes a first mixture formed on at least a part of the surface of the active material particles, and a second mixture spanning between two active material particles.

[0027] The negative electrode may have an active material layer on a negative electrode current collector. The active material layer may be formed on only one side of the negative electrode current collector, or on both sides. The negative electrode current collector is, for example, a metal foil made of a copper material such as copper or a copper alloy.

[0028] The active material layer includes active material particles for a negative electrode. The active material particles include metal-based particles and carbon-based particles, and may include active material particles other than metal-based particles and carbon-based particles. The total content of the carbon-based particles and metal-based particles in the active material particles may be 90 to 100% by weight, 90 to 99% by weight, or 92 to 95% by weight based on the total amount of the active material particles. The content ratio of the carbon-based particles to the metal-based particles in the active material particles, carbon-based particles:metal-based particles (weight ratio), may be 70:30 to 95:5, 80:20 to 92:8, or 85:15 to 95:5.

[0029] When active material layers are formed on both sides of the negative electrode current collector, the weight of the active material layers on each side (total of both sides) is, for example, 150 to 250 g / m 2 and 170 to 230 g / m 2 and 180 to 210 g / m 2 The weight per surface of the negative electrode current collector may be, for example, half of the weight per surface of both surfaces described above. The thickness of the active material layer per surface may be, for example, 90 to 200 μm, 100 to 180 μm, or 120 to 150 μm. The packing density of the active material layer can be calculated by the following formula, and may be, for example, 1.3 to 1.9 g / cc, 1.4 to 1.8 g / cc, or 1.5 to 1.7 g / cc.

[0030] Packing density [g / cc] = active material layer weight [g / m 2 ] / active material layer thickness [μm] The metal-based particles include particles of metal elements such as metal simple substances or metal oxides containing an element selected from the group consisting of silicon (Si), tin (Sn), antimony (Sb), bismuth (Bi), titanium (Ti), and germanium (Ge). The metal-based particles preferably include or are one or more particles selected from the group consisting of Si, SiOx (x=0.5-1.5), a composite of Si and C (hereinafter also referred to as "SiC composite"), and Sn, and more preferably are one or more particles selected from the group consisting of Si, SiOx, and a SiC composite. The metal-based particles are more preferably SiC composite particles. The SiC composite is, for example, a composite in which Si is dispersed in a carbon matrix.

[0031] The carbon-based particles preferably include or are one or more particles selected from the group consisting of carbon (C) such as graphite, hard carbon, soft carbon, and amorphous coated graphite, and are preferably graphite particles. The average particle diameter D50 of the graphite particles may be 5 to 20 μm, 8 to 10 μm, or 10 to 15 μm. The average particle diameter D50 in this specification is the particle diameter at which the cumulative frequency from the smaller particle diameter in the volume-based particle size distribution is 50%. The volume-based particle size distribution can be measured by a laser diffraction particle size distribution measuring device. The specific surface area (BET) of the graphite particles is 1.0 m 2 / g or more 3.0m 2 / g or less, and 2 / g or more 2.5m 2 The specific surface area can be calculated by the BET multipoint method on an adsorption isotherm measured by a gas adsorption method using a fully automatic specific surface area meter or the like.

[0032] The CNT may be a single-walled carbon nanotube (hereinafter also referred to as "SWCNT") or a multi-walled carbon nanotube such as a double-walled carbon tube (DWCNT). From the viewpoint of having fewer defects in the CNT structure and being easy to obtain CNTs with a large G / D ratio, the CNT is preferably a SWCNT.

[0033] The G / D ratio of the CNT is 30 or more, may be 40 or more, may be 50 or more, may be 30 to 200, may be 40 to 180, or may be 50 to 150. The G / D ratio is a value determined by Raman spectroscopy. In the Raman spectrum of the CNT, -1 The Raman shift seen around 1350 is called the G band, which is derived from graphite. -1 The Raman shift observed around the G / D ratio is called the D band, which is derived from defects in amorphous carbon or graphite. From this, it can be said that the CNT with a larger G / D ratio has higher crystallinity and greater strength. When a slurry containing CNTs, active material particles, and a first binder is used to form an active material layer as described later, the above components may be kneaded by applying a strong shearing force to enhance the dispersibility of the CNTs. By using CNTs with a G / D ratio in the above range, it is possible to prevent the CNTs from being torn off during kneading of the above components, thereby preventing the length of the CNTs from being shortened. This allows good conductive paths to be formed between the active material particles, thereby improving the cycle characteristics of the secondary battery. The G / D ratio in this specification is defined as the ratio between 1550 and 1650 cm in the Raman spectrum of CNTs. -1 The maximum peak intensity in the range of 1300 to 1400 cm is defined as G. -1 The maximum peak intensity within this range was calculated as D. The G / D ratio of the CNTs can be determined by the procedure described in the Examples below.

[0034] The average length of the CNTs in the active material layer is 1.4 μm or more, may be 1.5 μm or more, may be 1.6 μm or more, may be 1.7 μm or more, may be 2.0 μm or more, or may be 2.5 μm or more. The average length of the CNTs may be 1.4 to 5.0 μm, may be 1.5 to 3.0 μm, or may be 2.0 to 2.5 μm. The average length of the CNTs can be determined by analyzing SEM images as described in the examples below. It is believed that the presence of CNTs with the above average length in the active material layer can form a good conductive path between the active material particles, thereby improving the cycle characteristics of the secondary battery.

[0035] The CNTs in the active material layer may have a direct current resistance at 25° C. when dispersed in a 0.4 wt % aqueous solution within the range explained in the method for producing a negative electrode described below.

[0036] The content of CNT in the active material layer may be 0.01 to 1 part by weight, 0.05 to 0.1 parts by weight, or 0.1 to 0.5 parts by weight, relative to 100 parts by weight of the active material particles.

[0037] The first binder may be one or more selected from the group consisting of cellulose-based binders such as carboxymethyl cellulose (hereinafter also referred to as "CMC"), methyl cellulose (hereinafter also referred to as "MC"), and hydroxypropyl cellulose, and polyacrylic acid (hereinafter also referred to as "PAA"). The first binder preferably contains at least one of CMC and PAA, and more preferably contains CMC and PAA. CMC, MC, and PAA may be in the form of an acid or a salt, but are preferably in the form of a salt. Examples of the salt include alkali metal salts such as potassium and sodium.

[0038] The content of the first binder in the active material layer may be 0.5 to 5 parts by weight, 1 to 4 parts by weight, or 2 to 3 parts by weight, relative to 100 parts by weight of the active material particles. When two or more types of first binders are used, the content of the first binders refers to the total amount thereof.

[0039] The mixture refers to a state in which CNTs and the first binder are mixed and entangled with each other. The mixture does not include a state in which CNTs are attached to the surface of the layer formed by the first binder. The mixture includes a first mixture and a second mixture. In the active material layer, the first mixture and the second mixture may be connected and integrated, or may not be integrated. In addition to the integrated first mixture and second mixture, the second mixture may include the first mixture that is not integrated. Both ends of the second mixture that bridges between the active material particles may be formed on the surface of the active material particles. In this case, in this specification, the range of the same diameter as the diameter of the bridge portion (the portion that bridges between two active material particles) among the parts of the second mixture that contact the active material particles is included in the second mixture but not included in the first mixture, and the parts that contact the active material particles outside this range are included in the first mixture but not included in the second mixture.

[0040] The first mixture can be formed so as to be in direct contact with the surface of the active material particle. The first mixture may be formed on at least a part of the surface of the active material particle, and may be formed, for example, so as to be dotted on the surface of the active material particle, or so as to cover the entire surface of the active material particle. By having the first mixture, it is easier to ensure electrical connection points between the active material particle and the CNT, compared to when the CNT is disposed on the surface of the first binder layer formed on the surface of the active material particle, and therefore it is easier to reduce the input / output resistance when the present negative electrode is used in a secondary battery.

[0041] The second mixture is formed so as to bridge the gap between the two active material particles, as shown in the dashed circle in Figures 1 and 2. Both ends of the second mixture can be formed so as to be in direct contact with the surfaces of the two active material particles. Since the second mixture can form a conductive path between the active material particles, a secondary battery using this negative electrode can have excellent cycle characteristics.

[0042] The active material layer containing the first mixture and the second mixture can be obtained by adjusting the conditions, such as the order in which the CNTs are mixed and the solids concentration when mixing the CNTs, when preparing a slurry used to form the active material layer (described later).

[0043] In addition to the CNTs present as a mixture, the active material layer may contain CNTs that are not present as a mixture, i.e., that are not mixed with the first binder. The ratio of CNTs present in the first mixture and the second mixture to the total amount of CNTs in the active material layer (hereinafter also referred to as "CNT ratio") is preferably 40% or more, more preferably 45% or more, or may be 50% or more. The CNT ratio is preferably 40 to 90%, may be 45 to 80%, or may be 50 to 70%. When the CNT ratio is within the above range, it becomes easier to secure electrical connection points between the active material particles and the CNTs, so that the input / output resistance when the present negative electrode is used in a secondary battery can be further reduced. The CNT ratio can be determined by analyzing an SEM image of the active material layer as described in the examples below.

[0044] Methods for adjusting the CNT ratio to the above range include adjusting the order in which the CNTs are mixed and the conditions such as the solid content concentration when mixing the CNTs when preparing the slurry used to form the active material layer. In the active material layer obtained by carrying out the first step (1) described below (FIG. 1), it is easy to adjust the CNT ratio to the above range, and the entanglement between the CNTs and the first binder in the second mixture also tends to be large. On the other hand, in the active material layer obtained by carrying out the first step (2) described below (FIG. 2), it is difficult to adjust the CNT ratio to the above range, and the entanglement between the CNTs and the first binder in the second mixture also tends to be small.

[0045] The active material layer may contain, in addition to the active material particles, CNTs, and the first binder, a second binder other than the first binder, and a conductive material other than CNTs. When the first binder contains at least one of CMC and PAA, or is at least one of CMC and PAA, the second binder may contain at least one of styrene butadiene rubber (SBR) and polyvinyl alcohol (PVA), and preferably contains SBR. Examples of conductive materials other than CNTs include carbon materials such as carbon black (e.g., acetylene black, ketjen black), coke, and activated carbon.

[0046] (Method of manufacturing negative electrode) Fig. 3 is a flow chart showing a method for manufacturing a negative electrode according to an embodiment. The method for manufacturing a negative electrode according to this embodiment can manufacture a negative electrode for a secondary battery, and can also manufacture the present negative electrode. The method for manufacturing a negative electrode includes a first step of preparing a slurry, and a second step of forming an active material layer of the negative electrode using the slurry (Fig. 3). The slurry contains active material particles, a first binder, CNTs, and water. The active material particles contain metal-based particles and carbon-based particles, and the G / D ratio of the CNTs is 30 or more.

[0047] The slurry prepared in the first step includes active material particles, a first binder, CNTs, and water. The solid content of the slurry may be 35 to 55% by weight, 40 to 50% by weight, or 43 to 48% by weight. The metal particles and carbon particles may include the above-mentioned materials. The first binder may include the above-mentioned materials.

[0048] Examples of CNTs include those mentioned above, and SWCNTs are preferred. The G / D ratio of CNTs can be within the range described above. The DC resistance at 25°C when CNTs are dispersed in a 0.4% by weight aqueous solution is preferably 2000Ω or less, may be 1900Ω or less, may be 1800Ω or less, may be 1700Ω or less, may be 500 to 2000Ω, may be 700 to 1900Ω, may be 1000 to 1800Ω, or may be 1000 to 1700Ω. CNTs having a DC resistance within the above range have excellent conductivity, and therefore can form a good conductive path between the active materials of the active material layer. The DC resistance can be measured by the procedure described in the examples described below.

[0049] The slurry may further contain a second binder and a conductive material other than CNTs. Examples of the second binder and conductive material include the materials described above.

[0050] The first step may be the first step (1) or the first step (2) described below. By using the first step (1) or the first step (2), it is easy to obtain a negative electrode having a G / D ratio of 30 or more, an average length of the CNTs in the active material layer of 1.4 μm or more, and an active material layer containing the first mixture and the second mixture. From the viewpoint of obtaining an active material layer having the above-mentioned CNT ratio, the first step is preferably the first step (1).

[0051] The second step is a step of forming an active material layer using the slurry prepared in the first step. The second step may include a step of applying the slurry onto a negative electrode current collector to form a coating layer, drying the coating layer, and may further include a step of compressing the coating layer after drying. The negative electrode current collector may be made of the above-mentioned materials.

[0052] The first step (1) may include a step (1b) of obtaining a first kneaded body (kneaded body) by kneading the active material particles, the first binder, the CNTs, and water at a solid content rate in the range of 60 to 65% by weight, and a step (1c) of further adding water to the first kneaded body and kneading it. In the step (1b), the active material particles, the first binder, and the CNTs are kneaded at a relatively high solid content rate, and then the step (1c) is performed. As a result, the first binder and the CNTs are well entangled, making it easier to adjust the CNT ratio present in the first mixture to the above range, and making it easier to ensure electrical connection points between the active material particles and the CNTs. In addition, the entanglement between the CNTs and the first binder in the second mixture is also likely to be large. Therefore, by using a negative electrode manufactured by a manufacturing method including the first step (1), a secondary battery having excellent cycle characteristics and reduced input / output resistance is easily obtained.

[0053] The solid content in step (1b) (solid content in the first kneaded body) is preferably 60 to 65% by weight, and may be 61 to 65% by weight, 62 to 65% by weight, or 63 to 64% by weight. By setting the solid content in step (1b) within the above range, the CNT ratio can be easily adjusted to the above range, and the entanglement of the CNTs and the first binder in the second mixture can be easily increased.

[0054] The first step (1) may include a step (1a) of dry-mixing the active material particles and the first binder to obtain a mixture before the step (1b). When the first step (1) includes the step (1a), the step (1b) may obtain a first kneaded body by kneading the mixture, CNTs, and water. The first step (1) may include a step (1c) of further adding water to the first kneaded body and kneading the mixture. The step (1c) may include a step of kneading the second binder together with the first kneaded body and water. In this case, the kneading order of the first kneaded body, the second binder, and water in the step (1c) is not particularly limited, and they may be kneaded together, or the first kneaded body and water may be kneaded first, and then the second binder may be added and kneaded.

[0055] The first step (1) may be performed using a stirrer having a stirring blade. The rotation speed of the stirring blade in each step included in the first step (1) is not particularly limited. The rotation speed of the stirring blade in step (1b) may be 60 rpm or less, 50 rpm or less, 40 rpm, 10 to 60 rpm, 20 to 50 rpm, or 30 to 40 rpm. Since the manufacturing method of this embodiment uses CNTs with a large G / D ratio, even if the kneading in step (1b) is performed at the above rotation speed, it is possible to suppress the CNTs from being torn off. This allows a good conductive path to be formed in the active material layer, thereby improving the cycle characteristics of the secondary battery. The kneading time in step (1b) may be 10 to 200 min, 70 to 150 min, or 80 to 120 min.

[0056] The rotation speed of the stirring blade in step (1c) may be 50 rpm or less, 40 rpm or less, 30 rpm, 5 to 50 rpm, 10 to 40 rpm, or 20 to 30 rpm. The kneading time in step (1c) may be, for example, 10 to 180 minutes, 20 to 150 minutes, or 30 to 120 minutes.

[0057] The first step of the method for producing a negative electrode may be performed by the first step (2) described below instead of the first step (1). The first step (2) may include a step (2b) of kneading active material particles, a first binder, and water to obtain a second kneaded body, a step (2c) of kneading the second kneaded body and CNT to obtain a third kneaded body, and a step (2d) of adding water to the third kneaded body and kneading it. In the first step (2), the active material particles and the first binder are kneaded, and then the CNTs are added and kneaded, so that the CNTs can be dispersed in a short time. As a result, compared to the case of production in the first step (1), the first binder is more likely to adhere to the surface of the active material particles than to be mixed with the CNTs, and the CNTs are more likely to adhere to the first binder on the surface of the active material particles. Therefore, it is difficult to adjust the CNT ratio present in the first mixture and the second mixture to the above range, and the entanglement of the CNTs and the first binder in the first mixture and the second mixture is likely to be small. As a result, the input / output resistance of the negative electrode produced in the first step (2) tends to be larger than that of the negative electrode produced in the first step (1).

[0058] The solid content in step (2b) (solid content of the second kneaded body) is preferably 60 to 65% by weight, may be 61 to 65% by weight, may be 62 to 65% by weight, or may be 63 to 64% by weight.

[0059] The first step (2) may include a step (2a) of dry-mixing the active material particles and the first binder to obtain a mixture before the step (2b). When the first step (2) includes the step (2a), the step (2b) may include kneading the mixture and water to obtain a second kneaded body.

[0060] The solid content in step (2c) (the solid content of the third kneaded body) is, for example, more than 55% by weight and less than 60% by weight, and may be 56 to 59% by weight, or 57 to 58% by weight.

[0061] Step (2d) may include a step of kneading the second binder together with the third kneaded body and water. In step (2d), the order of kneading the third kneaded body, the second binder, and water is not particularly limited, and they may be kneaded together, or the third kneaded body and water may be kneaded first, and then the second binder may be added and kneaded.

[0062] The first step (2) may be carried out using a stirrer having a stirring blade. The rotation speed of the stirring blade in each step included in the first step (2) is not particularly limited. For example, the rotation speed of the stirring blade in step (2b) may be 10 to 65 rpm, 20 to 60 rpm, or 30 to 55 rpm. The kneading time in step (2b) may be, for example, 10 to 200 min, 70 to 150 min, or 80 to 120 min.

[0063] The rotation speed of the stirring blade in step (2c) may be 20 to 65 rpm, 30 to 60 rpm, or 40 to 55 rpm. The kneading time in step (2c) may be, for example, 5 to 60 minutes, 10 to 30 minutes, or 10 to 20 minutes.

[0064] The rotation speed of the stirring blade in step (2d) may be 5 to 50 rpm, 10 to 40 rpm, or 20 to 30 rpm. The kneading time in step (2d) may be, for example, 10 to 90 minutes, 15 to 60 minutes, or 30 to 45 minutes.

[0065] (Nonaqueous electrolyte secondary battery) The nonaqueous electrolyte secondary battery of this embodiment (hereinafter also referred to as "the battery") includes the present negative electrode, and typically includes an electrode assembly including the present negative electrode, and a nonaqueous electrolyte. The battery may have a battery case that houses the electrode assembly and the nonaqueous electrolyte. The battery case may include an exterior body having an opening, and a sealing plate that seals the opening. The exterior body and the sealing plate are preferably made of metal, and may be formed using aluminum, an aluminum alloy, iron, an iron alloy, or the like, and may be formed using, for example, an aluminum laminate film. A resin sheet serving as an electrode holder may be disposed between the electrode body and the exterior body.

[0066] The electrode body may include the present negative electrode, a positive electrode, and a separator. In the electrode body, the active material layer of the present negative electrode and the positive electrode active material layer of the positive electrode face each other via the separator. The electrode body may be a laminated type in which the present negative electrode, the positive electrode, and the separator are laminated, or a wound type in which a laminate in which the present negative electrode, the positive electrode, and the separator are laminated is wound.

[0067] The positive electrode usually has a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector is, for example, a metal foil made of an aluminum material such as aluminum or an aluminum alloy. The positive electrode active material layer contains positive electrode active material particles, and may further contain a conductive material, a binder, and the like. The positive electrode active material particles include, for example, layered or spinel-based lithium transition metal oxides (e.g., LiNiCoMnO2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi 0.5 Mn 1.5 O4, LiCrMnO4, LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of the conductive material include carbon materials such as fibrous carbon (CNT (SWCNT, DWCNT)), carbon black (e.g., acetylene black, ketjen black), coke, and activated carbon. Examples of the binder include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), and SBR.

[0068] The separator may have a substrate and a functional layer on at least one side of the substrate. The substrate may be a film made of a resin such as polyethylene, polypropylene, polyester, cellulose, polyamide, or the like, or a porous sheet such as a nonwoven fabric. The substrate may have a single-layer structure or a multi-layer structure. Examples of the functional layer include an adhesive layer and a heat-resistant layer, and the separator may have one or both of these. The adhesive layer may be formed, for example, by an adhesive. The heat-resistant layer may include, for example, a filler and a binder.

[0069] The non-aqueous electrolyte is preferably a non-aqueous solvent such as an organic solvent containing a supporting salt. Examples of the supporting salt include LiPF6, LiBF4, LiClO4, LiFSO3, and LiBOB (lithium bis(oxalato)borate). The non-aqueous electrolyte may contain one or more of these supporting salts. Examples of the non-aqueous solvent include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate (PC), butylene carbonate (BC), and diethyl carbonate (DEC). The non-aqueous electrolyte may contain one or more of these non-aqueous solvents.

[0070] (Method of manufacturing non-aqueous electrolyte secondary battery) The method for producing the present battery includes a step of producing a negative electrode by the method for producing a negative electrode of the present invention. The method for producing the present battery may further include a step of obtaining an electrode assembly using the present negative electrode, a positive electrode, and a separator, and a step of housing the electrode assembly and a nonaqueous electrolyte in a battery case. EXAMPLES

[0071] The present disclosure will be described more specifically below with reference to examples and comparative examples. Example 1 (Preparation of negative electrode: Preparation by the first step (1)) Graphite particles were used as the carbon particles, and composite particles of Si and C (SiC composite particles) were used as the metal particles. The average particle diameter D50 of the graphite particles was 17 μm, and the specific surface area (BET) of the graphite particles was 2.2 m 2 The CNTs had a G / D ratio and a DC resistance when dispersed in 0.4 wt % water, as shown in Table 1. Slurry (1) was prepared using a mixer (PRIMIX Hivismix 2P-1) according to the following procedure.

[0072] First, carbon-based particles, metal-based particles, CMC and PAA as the first binder were dry-mixed to obtain a mixture (step (1a)). Next, CNT (water-soluble paste with a solid content of 1% by weight) and water were added to the mixture to make the solid content 64% by weight, and the mixture was kneaded for 90 minutes at a stirrer speed of 50 rpm to obtain a first kneaded body (step (1b)). Water was further added to the first kneaded body and the mixture was kneaded for 30 minutes at a stirrer speed of 30 rpm, and then SBR was added as the second binder and the mixture was kneaded for 5 minutes at a stirrer speed of 30 rpm (step (1c)) to obtain a slurry (1) with a solid content of 46% by weight. The compounding ratio of the slurry (1) was graphite particles: SiC composite particles: CNT: CMC: PAA: SBR = 91: 9: 0.05: 1: 1: 1 (weight ratio).

[0073] The slurry (1) obtained above was applied to both sides of a copper foil having a thickness of 8 μm as a negative electrode current collector, dried, and compressed to obtain a negative electrode (1). The active material layer of the negative electrode (1) had a basis weight (total basis weight of both sides) of 195 g / m 2 The active material layer had a thickness (per side) of 130 μm and a packing density of 1.52 g / cc. The active material layer of the negative electrode (1) contained the first mixture and the second mixture.

[0074] (Preparation of positive electrode) The positive electrode active material particles were lithium nickel cobalt manganese composite oxide (NCM), the conductive material was acetylene black (AB), and the binder was polyvinylidene fluoride (PVdF) in a ratio of positive electrode active material particles:AB:PVdF=100:1:1 (weight ratio), which was mixed with N-methylpyrrolidone (NMP) as a solvent to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was applied to an aluminum foil with a thickness of 15 μm as a positive electrode current collector, dried, and compressed to obtain a positive electrode.

[0075] (Preparation of non-aqueous electrolyte secondary battery) Leads were attached to the negative and positive electrodes obtained above, and the negative and positive electrodes were laminated with a separator between them to obtain an electrode body. The electrode body was inserted into an exterior body made of an aluminum laminate sheet, a non-aqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a test cell (laminated cell) (1). The non-aqueous electrolyte was a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of EC:EMC:DMC=20:40:40, in which LiPF6 was dissolved as a lithium salt at a concentration of 1 mol / L.

[0076] Example 2 (Preparation of negative electrode: Preparation by the first step (2)) A slurry (2) was prepared by the following procedure to obtain a negative electrode (2). In this example, the same carbon-based particles, metal-based particles, CNTs, first binder, second binder, and stirrer as those used in the preparation of the negative electrode in Example 1 were used.

[0077] First, carbon-based particles (graphite particles), metal-based particles (SiC composite particles), and a first binder (CMC and PAA) were dry-mixed to obtain a mixture (step (2a)). Next, water was added to the mixture to make the solid content 64% by weight, and the mixture was kneaded for 90 minutes at a stirrer speed of 50 rpm to obtain a second kneaded body (step (2b)). Next, CNT (a water-soluble paste with a solid content of 1% by weight) was added to the second kneaded body, and the mixture was kneaded for 15 minutes at a solid content of 54% by weight and a stirrer speed of 50 rpm to obtain a third kneaded body (step (2c)). Further water was added to the third kneaded body, and the mixture was kneaded for 30 minutes at a stirrer speed of 30 rpm, and then the second binder (SBR) was added and the mixture was kneaded for 5 minutes at a stirrer speed of 30 rpm (step (2d)) to obtain a slurry (2) with a solid content of 46% by weight. Except for using the slurry (2) instead of the slurry (1), the negative electrode (2) was obtained in the same manner as in the preparation of the negative electrode of Example 1. The active material layer of the negative electrode (2) contained the first mixture and the second mixture.

[0078] (Preparation of non-aqueous electrolyte secondary battery) A test cell (2) was obtained in the same manner as in the preparation of the nonaqueous electrolyte secondary battery of Example 1, except that the negative electrode (2) was used instead of the negative electrode (1).

[0079] Comparative Example 1 A negative electrode (c1) and a test cell (c1) were obtained by the procedure described in Example 1, except that CNTs having the G / D ratio and DC resistance when made into a 0.4 wt % aqueous dispersion shown in Table 1 were used instead of the CNTs used in Example 1.

[0080] Comparative Example 2 A negative electrode (c2) and a test cell (c2) were obtained by the procedure described in Example 2, except that CNTs having the G / D ratio and DC resistance when made into a 0.4 wt % aqueous dispersion shown in Table 1 were used instead of the CNTs used in Example 2.

[0081] [Determination of G / D ratio of CNTs] The CNT dispersion liquid was dispensed onto a cover glass, and a Raman spectrum was obtained by irradiating a 300 μm diameter area with a laser beam having an excitation wavelength of 532 nm using a Raman microscope (manufactured by Horiba, Ltd.). -1 The maximum peak intensity in the range of 1300 to 1400 cm is defined as G. -1 The maximum peak intensity within this range was defined as D, and the G / D ratio was calculated. The results are shown in Table 1.

[0082] [Measurement of DC resistance of CNT] A 0.4 wt% aqueous dispersion of CNT (solid content 1 wt%) was poured into the measurement container of the LCR meter and test fixture (manufactured by Hioki E.E.C.) and left to stand for 24 hours. After that, AC impedance measurements were performed at 25°C with measurement frequencies of 4 Hz to 10 MHz, and DC resistance (DCR) was measured using a dedicated analysis system. The results are shown in Table 1.

[0083] [Determination of average CNT length and CNT percentage] (SEM image acquisition) Using a scanning transmission electron microscope (SEM, Hitachi High-Technologies) at an accelerating voltage of 1 kV, the surface of the negative electrode active material layer was confirmed by SEM images with a field of view of 9 × 7 μm.

[0084] (Determination of the average length of CNTs) The CNTs in the SEM image were painted in lines using image software, the perimeter of the lines was measured, and half of the perimeter was taken as the length of the CNTs. Since CNTs have an aspect ratio in which the length is extremely long relative to the diameter, the width of the lines influencing the perimeter can be ignored. The lengths of all the CNTs in the SEM image were determined, and the average value was taken as the average length of the CNTs. The results are shown in Table 1. Although the average length of the CNTs in Comparative Examples 1 and 2 is not shown, it is believed that the CNTs used in Comparative Examples 1 and 2 had a small G / D ratio, and therefore the CNTs became short during the preparation of the slurry, making them difficult to observe in the SEM image.

[0085] (Determination of CNT ratio) The percentages [%] of CNTs present in the first mixture and the second mixture (CNT percentage [%]) were calculated according to the following formula for all CNTs in the SEM images obtained above. The results are shown in Table 1.

[0086] CNT ratio [%] = (area of ​​CNTs present in the first mixture and the second mixture in the SEM image / area of ​​all CNTs in the SEM image) × 100 [Evaluation of initial efficiency] In an environment of 25°C, the test cell was charged to 4.2V at a current value of 0.05C (CC charging), and then discharged to 2.5V at a current value of 0.05C (CC discharging) for one cycle. The initial efficiency [%] was calculated from the discharge capacity at the first cycle and the charge capacity at the first cycle according to the following formula. The results are shown in Table 1.

[0087] Initial efficiency [%] = (1st cycle discharge capacity / 1st cycle charge capacity) x 100 [Evaluation of input / output resistance] (Calculating the input resistance) In a 25℃ environment, the test cell was charged at a current value of 0.33C until the state of charge (SOC) reached 50%, then charged at a constant current / constant voltage charge (CCCV) at a current value of 0.33C until the state of charge reached 50%, and then rested for 30 minutes. After that, the input resistance was calculated by measuring the IV (current and voltage) when charging at a current value of 0.2C for 10 seconds. The results are shown in Table 1.

[0088] (Calculating the output resistance) In a 25℃ environment, the test cell was charged at a current value of 0.33C until the state of charge (SOC) reached 50%, then charged at a constant current / constant voltage charge (CCCV) at a current value of 0.33C until the state of charge reached 50%, and then rested for 30 minutes. After that, the output resistance was calculated by measuring the IV (current and voltage) when discharging for 10 seconds at a current value of 0.2C. The results are shown in Table 1.

[0089] [Evaluation of cycle characteristics] In an environment of 25°C, the test cell was repeatedly charged to 4.2V by constant current / constant voltage charging (CCCV) at a current value of 0.33C, and then discharged to 2.5V at a current value of 0.33C (CC discharge), with this being one charge / discharge cycle. The capacity retention rate [%] was calculated as the discharge capacity at the 100th cycle relative to the discharge capacity at the 1st cycle according to the following formula. The results are shown in Table 1.

[0090] Capacity retention rate [%] = (discharge capacity at 100th cycle / discharge capacity at 1st cycle) x 100

[0091] [Table 1]

Claims

1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising: an active material layer including active material particles, carbon nanotubes, and a first binder; The active material particles include metal-based active material particles and carbon-based active material particles, The carbon nanotubes have a G / D ratio of 30 or more; the average length of the carbon nanotubes, as determined by analysis of a scanning transmission electron microscope image of the active material layer, is 1.4 μm or more; the active material layer includes a mixture of the carbon nanotubes and the first binder, The mixture includes a first mixture formed on at least a portion of the surface of the active material particles, and a second mixture spanning between two of the active material particles.

2. 2. The negative electrode of claim 1, wherein a ratio of the carbon nanotubes present in the first mixture and the second mixture to a total amount of the carbon nanotubes in the active material layer, as determined by analysis of the scanning transmission electron microscope image of the active material layer, is 40% or more.

3. 2. The negative electrode according to claim 1, wherein the metal-based active material particles include particles of one or more types selected from the group consisting of Si, SiOx, and a composite of Si and C.

4. The negative electrode according to claim 1 , wherein the metal-based active material particles include particles of a composite of Si and C.

5. The negative electrode according to claim 1 , wherein the carbon nanotubes are single-walled carbon nanotubes.

6. 2. The negative electrode of claim 1, wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.

7. the active material layer includes a second binder different from the first binder, The negative electrode of claim 6 , wherein the second binder comprises styrene butadiene rubber.

8. A non-aqueous electrolyte secondary battery comprising the negative electrode according to any one of claims 1 to 7.

9. A method for producing a negative electrode for a non-aqueous electrolyte secondary battery, comprising the steps of: A first step of preparing a slurry; A second step of forming an active material layer of the negative electrode using the slurry, the slurry includes active material particles, a first binder, carbon nanotubes, and water; The active material particles include metal-based active material particles and carbon-based active material particles, The carbon nanotubes have a G / D ratio of 30 or more.

10. The first step comprises: (1b) kneading the active material particles, the first binder, the carbon nanotubes, and water to obtain a kneaded body with a solid content in the range of 60 to 65% by weight; The method for producing a negative electrode according to claim 9 , further comprising the step (1c) of adding water to the kneaded body and kneading the mixture.

11. the first binder is at least one of carboxymethyl cellulose and polyacrylic acid; The step (1c) includes a step of kneading a second binder together with the kneaded body and the water, The method for producing a negative electrode according to claim 10 , wherein the second binder contains styrene-butadiene rubber.

12. The first step includes, prior to step (1b), a step (1a) of dry-mixing the active material particles and the first binder to obtain a mixture, The method for producing a negative electrode according to claim 10 , wherein the step (1b) comprises kneading the mixture, the carbon nanotubes, and water.

13. The method for producing a negative electrode according to claim 12, wherein the kneading in the step (1b) is carried out using a stirrer having a stirring blade under conditions in which the rotation speed of the stirring blade is 60 rpm or less.

14. The method for producing a negative electrode according to claim 9 , wherein a direct current resistance at 25° C. when the carbon nanotubes are dispersed in a 0.4% by weight aqueous solution is 2000Ω or less.

15. The method for producing a negative electrode according to claim 9 , wherein the metal-based active material particles contain one or more types of particles selected from the group consisting of Si, SiO x , and a composite of Si and C.

16. The method for producing a negative electrode according to claim 9 , wherein the first binder is at least one of carboxymethyl cellulose and polyacrylic acid.

17. A method for producing a non-aqueous electrolyte secondary battery, comprising the step of producing a negative electrode by the method for producing a negative electrode according to any one of claims 9 to 16.

Citation Information

Patent Citations

  • Manufacturing method of negative electrode for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2022072942A

  • Composition for forming negative electrode active material layer for lithium ion secondary battery

    JP2023076135A

  • Anti-phathgenesis composition and composition for preventing infectious diseases containing the same

    KR1020220112123A

  • Secondary battery negative electrode and secondary battery

    WO2021085255A1

  • Carbon nanotube dispersion liquid for electrode slurry, negative electrode slurry, nonaqueous electrolyte secondary battery, and manufacturing method for carbon nanotube dispersion liquid for electrode slurry

    WO2022138108A1